Abortion in the Structure of Causes of Maternal Mortality - Volkov, Valery G.; Granatovich, Nina N.; Survillo, Elena V.; Pichugina, Leontina V.; Achilgova, Zarina S. (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To study the structure of maternal mortality caused by abortion in the Tula region.Methods The medical records of deceased pregnant women, childbirth, and postpartum from January 01, 2001, to December 31, 2015, were analyzed.Results Overall, 204,095 abortion cases were recorded in the Tula region for over 15 years. The frequency of abortion was reduced 4-fold, with 18,200 in 2001 to 4,538 in 2015. The rate of abortions per 1,000 women (age 15–44 years) for 15 years decreased by 40.5%, that is, from 46.53 (2001) to 18.84 (2015), and that of abortions per 100 live births and stillbirths was 29.5%, that is, from 161.7 (2001) to 41.5 (2015). Five women died from abortion complications that began outside of the hospital, which accounted for 0.01% of the total number. In the structure of causes of maternal mortality for 15 years, abortion represented 14.3% of the cases. Lethality mainly occurred in the period from 2001 to 2005 (4 cases). Among the maternal deaths, many women died in rural areas after pregnancy termination at 18 to 20 weeks of gestation (n = 4). In addition, three women died from sepsis and two from bleeding.Conclusion The introduction of modern, effective technologies of family planning has reduced maternal mortality due to abortion.
Keywords: abortion; pregnancy; maternal mortality; family planning; sepsis